Contrastive Analysis of Rejection of Solicitation in Japanese and Banyumas Javanese - Rakhmah Riani Dwi Pratiwi; Susi Widianti (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
The The speech act of refusing is an action that can give an unpleasant feeling to the interlocutor. The speech act of refusing is motivated by a vertical relationship (jouge kankei) as well as a close relationship (shinso kankei) between the speaker and the interlocutor. This study aims to describe the comparison of speech acts of refusal in Japanese and Banyumas Javanese. In the work environment based on the relationship between the speaker and the interlocutor (jouge kankei and shinso kankei). This study used a descriptive research method with the Discourse Completion Test (DCT) instrument. The research object consists of native speakers of Banyumas Javanese and native speakers of Japanese. Based on the data analysis, it can be seen some similarities and differences in the strategies used by native speakers of Banyumas Javanese and Japanese in the work environment. In general, native speakers of Banyumas Javanese and native Japanese speakers use the strategies of {wabi}, {riyuu}, and {fuka} as the main strategies in refusal. However, several strategies are not used by native Japanese speakers, including {koshou} and {kantoushiteki hyoutsutsu} in rejecting close superiors and close friends. In using {riyuu}, native Javanese Banyumas speakers tend to use concrete and varied reasons, while native Japanese speakers use vague reasons. Judging from the politeness strategy according to Brown & Levinson (1987) the rejection strategy used by native Javanese speakers tends to use positive politeness while native Japanese speakers tend to use negative politeness strategies.